2016
DOI: 10.4143/crt.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Peroxisome Proliferator-Activated Receptor γ and TRAP220 in Patients with Operable Colorectal Cancer

Abstract: PurposeThe peroxisome proliferator-activated receptor γ (PPARγ) is a nuclear receptor that regulates expression of mediators of lipid metabolism and the inflammatory response. Thyroid hormone receptor-associated proteins 220 (TRAP220) is an essential component of the TRAP/Mediator complex. The objective of this study was to clarify whether PPARγ or TRAP220 are significant prognostic markers in resectable colorectal cancer (CRC).Materials and MethodsA total of 399 patients who underwent curative resection for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…4-hydroxy-2-nonenal increase PPAR gene expression and accelerate adiponectin protein degradation in adipocytes [ 65 ]. Peroxisome-proliferator-activated receptors has been also reported to arrest colorectal cancer proliferation [ 66 , 67 ], however it has also been linked to poor outcome in metastatic colorectal cancer (mCRC) [ 68 ]. 4-hydroxy-2-nonenal also upregulates prostaglandin E2 [ 69 ] and cyclooxygenase-2 (COX-2) [ 70 ], two factors associated with high proliferative colorectal cancer [ 71 ].…”
Section: Biologic Performances Of Obesitymentioning
confidence: 99%
“…4-hydroxy-2-nonenal increase PPAR gene expression and accelerate adiponectin protein degradation in adipocytes [ 65 ]. Peroxisome-proliferator-activated receptors has been also reported to arrest colorectal cancer proliferation [ 66 , 67 ], however it has also been linked to poor outcome in metastatic colorectal cancer (mCRC) [ 68 ]. 4-hydroxy-2-nonenal also upregulates prostaglandin E2 [ 69 ] and cyclooxygenase-2 (COX-2) [ 70 ], two factors associated with high proliferative colorectal cancer [ 71 ].…”
Section: Biologic Performances Of Obesitymentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma is a regulator of adipocyte differentiation 92 and has been implicated in the pathology of obesity, diabetes, and other disorders. 93 A meta-analysis comprising eight studies of 5,170 Caucasian and Asian patients reported that the rs1801282 (Pro12Ala) polymorphism Ala allele was negatively associated with DR in type 2 diabetes in Caucasians only ( P =0.01). 94 Similarly, a series of 573 Pakistani patients also reported a significant negative association between the Ala allele and PDR in type 2 diabetes (OR =0.4, 95% CI =0.2–0.8).…”
Section: Newer Candidate Genesmentioning
confidence: 99%
“…Three types of PPARs (α, β, and γ) have been identified thus far. The most studied subtype PPARγ, which was identified as a critical regulatory factor in adipogenesis, is also involved in islet cell sensitization, cell cycle arrest, and proliferation [ 8 ]. PPARγ agonist has been used for type II diabetes and related metabolic disease therapy, including obesity, hypertension, and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%